2016
DOI: 10.4995/eurocall.2016.6467
|View full text |Cite
|
Sign up to set email alerts
|

A study of Chinese engineering students’ communication strategies in a mobile-assisted professional development course

Abstract: The development of students' professional skills is an important issue in higher education in China. This research reports a 3-month study investigating engineering students' communication strategies (CSs) while they were interacting to do a 12-week mobile-assisted learning project, i.e., "Organizing and Attending a Model International Conference". This learning project was a major teaching module of the English course of Professional Applications, which used a blended teaching mode integrating face-to-face in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In the design, the students' learning psychology and their learning habits should be taken into consideration. The designed teaching strategies should adopt taskdriven, problem-oriented and other strategic activities as much as possible to stimulate the students' learning interests and thinking [15]. Second, it's essential to pay attention to the combination of the topic content and practical application, for instance, for the materials used, courseware, comments and others, it's necessary to fully consider the actual application environment and the actual needs of teaching, and constantly enrich and update the content.…”
Section: Design and Making Of Topic Selection For Micro Coursementioning
confidence: 99%
“…In the design, the students' learning psychology and their learning habits should be taken into consideration. The designed teaching strategies should adopt taskdriven, problem-oriented and other strategic activities as much as possible to stimulate the students' learning interests and thinking [15]. Second, it's essential to pay attention to the combination of the topic content and practical application, for instance, for the materials used, courseware, comments and others, it's necessary to fully consider the actual application environment and the actual needs of teaching, and constantly enrich and update the content.…”
Section: Design and Making Of Topic Selection For Micro Coursementioning
confidence: 99%
“…United Kingdom researcher Li [12] explored tourism and hospitality management students' perceptions of social media applications for formal and informal learning. Beijing University of posts and telecommunication researcher Cheng [11] conducted a three-month study to identify L2 learners' communication strategies. The findings revealed that Chinese engineering students used different kinds of communication strategies to complete academic assignment.…”
Section: Social Media Usage For Academic Purposementioning
confidence: 99%
“…Many prior studies on English CC have been conducted and concentrated on the aspect of students' CC (e.g., studies conducted by Cheng (2016); Clavel-Arroitia (2019); Hermosilla et al (2018); Komariah et al (2020); and Lee (2017)). However, our reviews of literature have ended up with a perception that there are still few studies on English CC with the foci central to English lecturers.…”
Section: Introductionmentioning
confidence: 99%